Legal Protection of Female Journalists over Gender Inequality during the Covid-19 Pandemic - Khairunnisa, Vena Lidya; Nurrobby, Mochammad Ilham (Universitas Negeri Semarang, 2021)
The purpose of this study was to find out the legal problems experienced by female journalists over gender inequality during the Covid-19 pandemic and to find out the legal protections to overcome these problems. The type of research used is a normative legal research type with an invitation approach and a historical approach. The findings in this paper are, during the Covid-19 pandemic, gender inequality towards female journalists has increased. It is still very rare for people to raise issues related to gender inequality experienced by female journalists. Examples of problems with a gender perspective in the media are the lack of involvement for women in journalism activities, marginalization and subordination positions for women in various fields, legitimacy regarding gender bias, dominating economic and political interests, regulations on media that are not sensitive to gender and between conventional journalism and gender. equality. The government in Indonesia officially adheres to the principle of equality as regulated in Article 27 of the 1945 Constitution of the Republic of Indonesia which states that all Indonesian citizens are equal before the law. Therefore, journalists must be able to enjoy gender and legal protection for the gender inequality they experience. It is necessary to reconstruct the law, considering that women have the same position as men in terms of their position, rights and obligations so that they have equal opportunities in various fields.